Modeling of skeet shooting technique with using of simulation exercises - Hrybovskyy, R.; Zanevskyy, I.; Hrybovskyy, V. (Journal of Physical Education and Sport, 2015)
The article explains the approaches to modeling technique of well-aimed shot in shotgun shooting. The aim was to develop a model technology at skeet shooting while performing simulation exercises. We used the following methods: data analysis and synthesis of library scientific and methodical resources, pedagogical observations, video analysis method and the method of numerical differentiation. We applied such computer technologies as MS Office Paint and Excel. We have developed special hardware and software systems to create a moving picture of the target and the aiming point placed vertically on the screen, which allows training in the form of dry shooting at skeet. It has been shown that to evaluate the simulation exercises technique you should determine the distance from aiming point to the center of the target, its horizontal and vertical components, and appropriate velocity relative and absolute values. We have given the ground to need of using of special simulation exercises in the training process at skeet.